Effort‐reward imbalance at work and weight changes in a nationwide cohort of workers in Denmark. Issue 7 (14th April 2020) - Nordentoft, Mads; Rod, Naja Hulvej; Bonde, Jens Peter; Bjorner, Jakob Bue; Cleal, Bryan; Larsen, Ann Dyreborg; Madsen, Ida E.H.; Magnusson Hanson, Linda L.; Nexo, Mette Andersen; Pedersen, Line Rosendahl Meldgaard; Sterud, Tom; Xu, Tianwei; et al.
Abstract: Objective: To investigate the relation between effort‐reward imbalance (ERI) at work and subsequent weight changes. Methods: We included participants from a population‐based cohort of workers in Denmark (mean age = 47 years, 54% women) with two (n = 9005) or three repeated measurements (n = 5710). We investigated the association between (a) ERI (ie, the mismatch between high efforts spent and low rewards received at work) at baseline and weight changes after a 2‐year follow‐up (defined as ≥5% increase or decrease in body mass index (BMI) vs stable), and (b) onset and remission of ERI and subsequent changes in BMI. Using multinomial logistic regression we calculated risk ratios (RR) and 95% confidence intervals (CI), adjusted for sex, age, education, cohabitation, migration background, and follow‐up time. Results: After 2 years, 15% had an increase and 13% a decrease in BMI. Exposure to ERI at baseline yielded RRs of 1.09 (95% CI: 0.95‐1.25) and 1.04 (95% CI: 0.90‐1.20) for the increase and decrease in BMI, respectively. There were no differences between sex and baseline BMI in stratified analyses. The onset of ERI yielded RRs of 1.04 (95% CI: 0.82‐1.31) and 1.15 (95% CI: 0.84‐1.57) for subsequent increase and decrease in BMI. The RRs for the remission of ERI and subsequent increase and decrease in BMI were 0.92 (95% CI: 0.71‐1.20) and 0.78 (95% CI: 0.53‐1.13), respectively. Of the ERI components, high rewards were associated with a lower risk of BMI increase. Conclusion: ERI was not a risk factor for weight changes. Future studies may investigate whether this result is generalizable to other occupational cohorts and settings.